2015
DOI: 10.1051/0004-6361/201526752
|View full text |Cite
|
Sign up to set email alerts
|

Recovering star formation histories: Integrated-light analyses vs. stellar colour–magnitude diagrams

Abstract: Context. Accurate star formation histories (SFHs) of galaxies are fundamental for understanding the build-up of their stellar content. However, the most accurate SFHs -those obtained from colour-magnitude diagrams (CMDs) of resolved stars reaching the oldest main-sequence turnoffs (oMSTO) -are presently limited to a few systems in the Local Group. It is therefore crucial to determine the reliability and range of applicability of SFHs derived from integrated light spectroscopy, as this affects our understanding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 101 publications
(169 reference statements)
5
36
0
Order By: Relevance
“…To recover the recent SFH in different regions of the central ring in NGC 3351 we use the full spectral fitting routine STECKMAP (STEllar Content and Kinematics via Maximum a Posteriori; Ocvirk et al 2006b,a). The justification and testing of this methodology is outlined in e.g., Sánchez-Blázquez et al (2011);Ruiz-Lara et al (2015), and our adopted methodology is described in detail in Sánchez-Blázquez et al (2014). In short, the integrated spectrum within a given spaxel is compared to a grid of composite stellar population models in order to recover the light weighted mass fractions in different age bins.…”
Section: Appendix B: Star Formation History Of Ngc 3351's Nuclear Ringmentioning
confidence: 99%
“…To recover the recent SFH in different regions of the central ring in NGC 3351 we use the full spectral fitting routine STECKMAP (STEllar Content and Kinematics via Maximum a Posteriori; Ocvirk et al 2006b,a). The justification and testing of this methodology is outlined in e.g., Sánchez-Blázquez et al (2011);Ruiz-Lara et al (2015), and our adopted methodology is described in detail in Sánchez-Blázquez et al (2014). In short, the integrated spectrum within a given spaxel is compared to a grid of composite stellar population models in order to recover the light weighted mass fractions in different age bins.…”
Section: Appendix B: Star Formation History Of Ngc 3351's Nuclear Ringmentioning
confidence: 99%
“…This extreme chemistry also makes the comparison with resolved stellar population studies less direct as the latter have generally studied less metal-rich systems (see e.g. Ruiz-Lara et al 2015Ocvirk 2010). Moreover, as described above, we allowed in our analysis for stellar populations older than the age of the Universe to account for model systematics (e.g.…”
Section: Stellar Population Analysismentioning
confidence: 99%
“…Other efforts along the same line of study have also been performed by Koleva et al (2008) and Riffel et al (2011), who concluded that SSP models quite satisfactorily reproduce the observed parameters, but that there were minor caveats. In the context of studying more complex objects with non-instantaneous star formation history, more recently Ruiz-Lara et al (2015) presented a comparison of resolved and unresolved stellar populations within a field in the Large Magellanic Cloud in a study of the star formation history in the region.…”
Section: Introductionmentioning
confidence: 99%